(untitled) (Interdisciplinary Studies Journal, 2025)
The present issue of the Revista de Estudos Interdisciplinares features the thematic dossier entitled Legal Transformations: Intersections between Culture, Technology and Sustainability, with the aim of gathering critical reflections on the multiple challenges currently affecting the normative field. The proposal starts from the recognition that we live in times marked by intense changes, where technological advances, ecological crises, and sociocultural reconfigurations demand broader and more articulated responses from justice systems. In this context, it becomes imperative to rethink traditional models of legal construction, fostering dialogue with other disciplines. This articulation aims to expand the analytical capacity of Law, enabling its effective engagement with the complexities that define the contemporary world. Thus, the present volume proposes an approach that transcends epistemological boundaries, promoting dialogue with areas such as computer science, anthropology, environmental sciences, education, public policy, and the arts.